Neutrophils, as "Trojan horses", participate in the delivery of therapeutical PLGA nanoparticles into a tumor based on the chemotactic effect. (1st January 2020) - Hao, Jifu; Chen, Junlan; Wang, Meixiang; Zhao, Jing; Wang, Jianze; Wang, Xingrong; Li, Yuhong; Tang, Hua
Abstract: Inspired by the fact that leukocytes have innate phagocytic functions and oriented migration capabilities in response to chemoattractants, we have unveiled that endogenous neutrophils as "Trojan horses", participate in the delivery of nanoparticles in an "i n vivo self-armed assembly" manner. Neutrophils were the main population to preferentially sequester the intravenous administrated nanoparticles with an average size of 260 nm. The pre-implantation of CXCL1-laden hydrogels could trigger and induce a targeted signal to attract an influx of neutrophils carrying the therapeutic goods to the desired position. In mouse models of melanoma, the combinatorial regimen of using the PLGA nanoparticles with the CXCL1 hydrogels exhibited superior tumor inhibition capability. This work leveraged the natural phagocytosis of neutrophile and the chemotactic effect of chemokines for targeted delivery. We believe this strategy will improve the therapeutic efficiency of nanoparticle-based delivery systems, especially when the chemokines are implanted at sites of surgical tumor removal, during cancer treatment at the clinic.